Analysis of Musculoskeletal Disorders in Electric Vehicle Prototype Drivers Using the Nordic Body Map Method - Reyvanda Ayusran; Wanda Afnison; Irzal Irzal; Milana Milana (Jurnal Vokasi Mekanika (VoMek), 2025)
The dwindling availability of fossil-based energy sources has spurred breakthroughs in the evolution of eco-conscious transportation, one of which is manifested in the Indonesian Electric Car Competition (Kompetisi Mobil Listrik Indonesia – KMLI). In this arena, collegiate teams engineer lightweight, single-occupant electric prototype vehicles emphasizing energy thrift. Nonetheless, spatial constraints and performance optimization frequently take precedence over ergonomic design, heightening the likelihood of musculoskeletal strain. This investigation seeks to examine bodily discomforts related to the musculoskeletal system as encountered by the operator of a prototype electric vehicle, employing the Nordic Body Map (NBM) assessment tool. The inquiry adopted a descriptive format via a focused case analysis involving the primary driver from the Megathrust Eco Team representing Universitas Negeri Padang (UNP) in the 2024 KMLI. Post-operation, the participant filled out the NBM form to denote discomfort regions, referencing a Likert-type scale from 1 (no pain) to 4 (extreme pain). The outcomes identified the cervical region, shoulders, dorsum, and lumbar zone as areas with elevated distress, classified under Pain and Intense Pain levels, thus revealing substantial ergonomic concerns. From these insights, it is inferred that the seating layout and cockpit geometry must be reconsidered and fine-tuned according to the driver’s anthropometric dimensions to alleviate physical complaints and boost vehicular comfort. The study aspires to aid in fostering electric vehicles that are more attuned to human-centered design, balancing well-being and operational safety.